Kompleksitas Operasi, Reputasi Kap, Ukuran Perusahaan, Leverage Terhadap Audit Report Lag Pada Perusahaan Sub Sektor Makanan Dan Minuman Tahun 2017-2020 - Sanova, Nur Khalipah; Malahayati, Rina; Aramana, Desi (Asosiasi Dosen Akuntansi Indonesia, 2022)
This study aims to test the complexity of operations, reputation of KAP, the size firm, leverage impact on audit report lag. The population in this study was a food and beverage sub-sector company during 2017-2020 which amounted to 30 companies. Data analysis in this study is descriptive statistics, Multiple Linear Regression analysis, R coefficient of determination, and tested T. The results showed that operating complexity and leverage had no effect on audit report lag whereas reputation and size firm had an effect on audit report lag.